A polymer magnetic bead with biomimetic micro-nano fractal structure and its preparation method and application

By constructing a burr-like hydrophilic micro-nano fractal structure on the surface of the immune magnetic beads, the problem of poor capture effect due to smooth surface of the existing magnetic beads is solved, and efficient capture of tumor cells and the like is achieved, and the preparation method is simple and easy to perform.

CN115677935BActive Publication Date: 2025-02-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110828235.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-22
Publication Date
2025-02-07
Estimated Expiration
2041-07-22

AI Technical Summary

Technical Problem

The surface of existing immune magnetic beads is smooth and it is difficult to construct and control micro-nano structures, resulting in unsatisfactory results in applications such as catching tumor cells.

Method used

Polymer magnetic beads with bionic micro-nano fractal structures are distributed on the surface of the polymer magnetic beads with burrs, which are similar to the structure on the surface of immune cells, improving the ability to capture tumor cells.

Benefits of technology

Through topological interaction and molecular recognition synergistic action, efficient capture of tumor cells, viruses and bacteria is achieved, and the preparation method is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115677935B_ABST
    Figure CN115677935B_ABST
Patent Text Reader

Abstract

The invention discloses a polymer magnetic bead with a bionic micro-nano fractal structure, comprising a hydrophobic polymer core, magnetic nanoparticles dispersed inside and on the surface of the core, and a hydrophilic micro-nano fractal structure distributed on the surface of the core. The burr-shaped hydrophilic micro-nano fractal structure on the surface of the magnetic bead is rough and has a large specific surface area, similar to the surface structure of immune cells, and forms a good topological interaction with tumor cells. The cells extend filamentous pseudopodia and entangle the micro-nano fractal structure, and the magnetic beads are used to efficiently capture tumor cells through the synergistic effect of structural matching and molecular recognition. At the same time, the preparation method of the magnetic beads is simple and easy to mass produce. A series of different micro-nano fractal structures can be obtained by regulating the preparation method to meet different needs. Therefore, the polymer magnetic beads have good application prospects in multiple fields such as immunoassay, nucleic acid separation and extraction, cell sorting, bacterial capture, virus capture, enzyme fixation, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of detection and separation materials, and more specifically to a polymer magnetic bead with a bionic micro-nano fractal structure and a preparation method and application thereof. Background Art

[0002] Immunomagnetic beads (IMB) are widely used in many fields such as immunoassay, nucleic acid separation and extraction, cell sorting, enzyme fixation, etc., and are key materials for detection and separation in the field of life sciences. Immunomagnetic beads have been approved by the U.S. Food and Drug Administration (FDA) and the China National Medical Products Administration (NMPA) as an important tool for clinical diagnosis of cancer. Commercial immunomagnetic beads represented by Dynabeads mainly rely on antigen-antibody interaction, but the effect on tumor cell detection is often not ideal. Studies have shown that the surface micro-nano structure is very important in the process of immune cells capturing tumor cells. The surface of the immunomagnetic beads prepared in the prior art is relatively smooth, and the micro-nano structure is difficult to construct and the structure is difficult to control. Therefore, there are still huge challenges in applying immunomagnetic beads to the preparation of chips for capturing tumor cells.

[0003] Therefore, it is necessary to provide a magnetic bead with a controllable surface micro-nano structure and a simple preparation method. Summary of the invention

[0004] An object of the present invention is to provide a polymer magnetic bead with a bionic micro-nano fractal structure. The surface of the magnetic bead is distributed with a micro-nano fractal structure, which has a burr-like morphology and mimics the structure of the surface of immune cells, greatly improving the ability of the magnetic bead to capture tumor cells.

[0005] Another object of the present invention is to provide a method for preparing polymer magnetic beads with bionic micro-nano fractal structures.

[0006] Another object of the present invention is to provide an application of polymer magnetic beads with bionic micro-nano fractal structures.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A polymer magnetic bead with a bionic micro-nano fractal structure comprises a hydrophobic polymer core, magnetic nanoparticles dispersed inside and on the surface of the core, and a hydrophilic micro-nano fractal structure distributed on the surface of the core.

[0009] The surface of the polymer magnetic beads provided by the present invention is a hydrophilic micro-nano fractal structure, which has a burr-like morphology and is a hydrophilic polymer chain. Therefore, the surface of the polymer magnetic beads in the present invention is different from the smooth state in the prior art, but is rough, has a large specific surface area, and forms a good topological interaction with tumor cells. The cells extend filopodia and entangle the micro-nano fractal structure; at the same time, the structure can also improve the capture efficiency of the polymer magnetic beads for viruses and bacteria.

[0010] Preferably, the hydrophilic micro-nano fractal structure has a burr-like morphology; the burr-like morphology can increase the roughness of the surface of the magnetic beads, increase the specific surface area, and increase the contact area with cells, bacteria, viruses, and other detection and separation substances.

[0011] Preferably, the length of the hydrophilic micro-nano fractal structure is 0 to 2500 nm, but excluding 0; the diameter is 50 nm to 300 nm;

[0012] For example, the length of the hydrophilic micro-nano fractal structure includes but is not limited to 1-2000 nm, 5-1500 nm, 20-1000 nm, 50-500 nm or 100-500 nm, etc.;

[0013] The diameter of the hydrophilic micro-nano fractal structure includes, but is not limited to, 60-280 nm, 70-250 nm, 80-230 nm, 100-200 nm, or 120-180 nm.

[0014] Preferably, the material of the hydrophilic bionic micro-nano fractal structure includes, but is not limited to, one or more of sodium polyacrylate, sodium polymethacrylate, sodium polyitaconate, sodium polymaleate, sodium polyvinyl sulfonate, sodium polystyrene sulfonate, sodium polystyrene carboxylate, and sodium polystyrene borate.

[0015] Preferably, the polymer magnetic beads have superparamagnetism and a particle size of 100 nm to 100 μm. The magnetic beads have a magnetic force sufficient for separation of substances.

[0016] Preferably, the diameter of the hydrophobic polymer core is 100 nm to 100 μm; the hydrophobic polymer core acts as a supporting skeleton. If the hydrophobic polymer is not added, the prepared magnetic beads will collapse and cannot be spherical.

[0017] Preferably, the material of the hydrophobic polymer core includes, but is not limited to, one or more of polystyrene, poly-α-methylstyrene, poly-o-chlorostyrene, polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride.

[0018] Preferably, the particle size of the magnetic nanoparticles is 1 nm to 1000 nm;

[0019] For example, the particle size of the magnetic nanoparticles includes but is not limited to 5nm to 900nm, 10nm to 800nm, 20nm to 700nm, 50nm to 500nm or 100nm to 400nm.

[0020] Preferably, the magnetic nanoparticles include but are not limited to one or more of ferroferric oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron platinum nanoparticles, cobalt triplatinide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles.

[0021] The present invention also provides a method for preparing the above-mentioned bionic micro-nano fractal polymer magnetic beads, which mainly comprises the following steps:

[0022] S1, dissolving a hydrophobic monomer, an initiator, and a hydrophobic polymer in an organic solvent to obtain a solution A; dispersing magnetic nanoparticles in an organic solvent to obtain a dispersion B; mixing the solution A and the dispersion B evenly, and emulsifying them by adding a surfactant aqueous solution to obtain an oil-in-water emulsion C;

[0023] S2, dissolving the hydrophilic monomer in an aqueous surfactant solution to obtain a solution D;

[0024] S3, mixing the oil-in-water emulsion C and the solution D, heating to volatilize the organic solvent, introducing nitrogen, and after the polymerization reaction, washing and freeze-drying the product to obtain.

[0025] In the preparation method provided by the present invention, the polymerization reaction occurs at the oil-water interface, the hydrophobic polymer is in the oil phase, and the hydrophilic polymer is in the water phase, and the two undergo polymerization reaction at the interface to obtain a hydrophobic polymer core and a micro-nano fractal structure distributed on its surface.

[0026] Preferably, the hydrophobic monomer includes, but is not limited to, one or more of styrene, α-methylstyrene, o-chlorostyrene, divinylbenzene, methyl methacrylate, and ethyl methacrylate.

[0027] Preferably, the initiator includes but is not limited to one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobiscyclohexylcarbonitrile, benzoyl peroxide, and tert-butyl perbenzoate.

[0028] Preferably, the hydrophobic polymer includes, but is not limited to, one or more of polystyrene, poly-α-methylstyrene, poly-o-chlorostyrene, polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride.

[0029] Preferably, the hydrophilic monomer includes, but is not limited to, one or more of sodium acrylate, sodium methacrylate, sodium itaconate, sodium maleate, sodium vinyl sulfonate, sodium styrene sulfonate, sodium styrene carboxylate, and sodium styrene borate.

[0030] Preferably, the organic solvent includes but is not limited to one or more of benzene, toluene, xylene, chlorobenzene, dichloromethane and chloroform.

[0031] Preferably, the surfactant includes, but is not limited to, one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, polyvinyl alcohol, and polyethylene glycol.

[0032] Preferably, the detergent used for washing the product in S3 includes, but is not limited to, one or more of methanol, ethanol, acetone, and deionized water.

[0033] Preferably, the weight average molecular weight of the hydrophobic polymer is 1000 g / mol to 80000 g / mol; and the concentration of the hydrophobic polymer in solution A is 0.05 mg / mL to 500 mg / mL.

[0034] Further preferably, the weight average molecular weight of the hydrophobic polymer includes but is not limited to 2000 g / mol to 70000 g / mol, 5000 g / mol to 60000 g / mol, 10000 g / mol to 50000 g / mol or 20000 g / mol to 40000 g / mol and the like.

[0035] The concentration of the hydrophobic polymer in the solution A includes, but is not limited to, 0.1 mg / mL to 500 mg / mL, 0.5 mg / mL to 400 mg / mL, 1.0 mg / mL to 300 mg / mL, 5.0 mg / mL to 200 mg / mL, or 10.0 mg / mL to 100 mg / mL.

[0036] Preferably, the mass ratio of the hydrophobic monomer to the magnetic nanoparticles used in the preparation process includes but is not limited to 10-300:1, 20-250:1, 50-200:1, 80-150:1 or 100:1.

[0037] Preferably, the molar ratio of the hydrophobic monomer to the hydrophilic monomer includes but is not limited to 0.1 to 200:1, 0.5 to 200:1, 1.0 to 150:1, 5.0 to 100:1 or 10.0 to 80:1, etc.

[0038] Preferably, the molar ratio of the initiator to the hydrophilic monomer includes but is not limited to 0.01-0.1:1, 0.02-0.09:1, 0.03-0.08:1, 0.04-0.07:1 or 0.05:1, etc.

[0039] Preferably, the concentration of the surfactant solution, i.e. the surfactant in water, includes but is not limited to 0.0001 g / mL to 0.05 g / mL, 0.0005 g / mL to 0.05 g / mL, 0.001 g / mL to 0.05 g / mL, 0.005 g / mL to 0.05 g / mL or 0.01 g / mL to 0.05 g / mL, etc.

[0040] Preferably, the volume ratio of the oil-in-water emulsion C to the solution D in S3 includes but is not limited to 1:0.01-1, 1:0.05-1, 1:0.1-1, 1:0.5-1 or 1:1, etc.

[0041] Preferably, after the oil-in-water emulsion C and solution D are mixed in S3,

[0042] The ratio of the molar amount of the hydrophobic monomer to the volume of the surfactant aqueous solution includes, but is not limited to, 0.005mmol~15mmol:1mL, 0.01mmol~15mmol:1mL, 0.05mmol~15mmol:1mL, 0.1mmol~15mmol:1mL, 0.5mmol~15mmol:1mL or 1mmol~15mmol:1mL, etc.

[0043] Preferably, the ratio of the molar amount of the initiator to the volume of the surfactant aqueous solution includes but is not limited to 0.003mmol~0.3mmol:1mL, 0.005mmol~0.3mmol:1mL, 0.01mmol~0.3mmol:1mL, 0.05mmol~0.3mmol:1mL or 0.1mmol~0.3mmol:1mL, etc.

[0044] Preferably, the ratio of the molar amount of the hydrophilic monomer to the volume of the surfactant aqueous solution includes but is not limited to 0.005mmol~15mmol:1mL, 0.01mmol~15mmol:1mL, 0.05mmol~15mmol:1mL, 0.1mmol~15mmol:1mL, 0.5mmol~15mmol:1mL or 1mmol~15mmol:1mL, etc.

[0045] Preferably, the suitable temperature for the process of preparing solution A and dispersion B in S1 is 15° C. to 35° C., and the time is 0.2 h to 24 h.

[0046] Preferably, the time for the organic solvent volatilization process in S3 is 5 min to 6 h, the time for introducing nitrogen is 3 min to 30 min, the polymerization reaction temperature is 55° C. to 90° C., and the polymerization reaction time is 45 min to 24 h.

[0047] The present invention also provides the use of the polymer magnetic beads with bionic micro-nano fractal structures in immunoassay, nucleic acid separation and extraction, cell sorting and enzyme fixation.

[0048] The beneficial effects of the present invention are as follows:

[0049] The present invention provides a polymer magnetic bead with a bionic micro-nano fractal structure, the surface of the magnetic bead is a burr-shaped hydrophilic micro-nano fractal structure, rough and large specific surface area, similar to the surface structure of immune cells, and forms a good topological interaction with tumor cells. The cells extend filamentous pseudopodia and entangle the micro-nano fractal structure, and the magnetic beads are used to efficiently capture tumor cells through the synergistic effect of structural matching and molecular recognition. At the same time, the preparation method of the magnetic beads is simple and easy to scale production. A series of different micro-nano fractal structures can be obtained by regulating the preparation method to meet different needs. Therefore, the polymer magnetic beads have good application prospects in multiple fields such as immunoassay, nucleic acid separation and extraction, cell sorting, bacterial capture, virus capture, enzyme fixation, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0051] Figure 1 The scanning electron microscope photograph of the polymer magnetic beads with biomimetic micro-nano fractal structure prepared in Example 1 of the present invention is shown.

[0052] Figure 2 A scanning electron microscope photograph of the polymer magnetic beads with biomimetic micro-nano fractal structure prepared in Example 2 of the present invention is shown.

[0053] Figure 3 The scanning electron microscope photograph of the polymer magnetic beads with biomimetic micro-nano fractal structure prepared in Example 3 of the present invention is shown.

[0054] Figure 4 A transmission electron microscope photograph of the polymer magnetic beads with biomimetic micro-nano fractal structure prepared in Example 3 of the present invention is shown.

[0055] Figure 5 A scanning electron microscope photograph of the polymer magnetic beads with biomimetic micro-nano fractal structure prepared in Example 4 of the present invention is shown.

[0056] Figure 6 The interaction between tumor cells and polymer magnetic beads with biomimetic micro-nano fractal structures in Application Example 1 is shown.

[0057] Figure 7 The graph shows how the capture efficiency of the polymer magnetic beads with bionic micro-nano fractal structures for tumor cells changes over time in Application Example 1.

[0058] Figure 8The capture efficiency of the polymer magnetic beads with biomimetic micro-nano fractal structure on different cells in Application Example 2 is shown.

[0059] Fig. 9 The effect of the ratio of polymer magnetic beads with bionic micro-nano fractal structure to tumor cells on the capture efficiency in Application Example 3 is shown.

[0060] Fig.10 The relationship between the capture efficiency of tumor cells by polymer magnetic beads in Application Example 4 and the length of the micro-nano fractal structure is shown. DETAILED DESCRIPTION

[0061] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0062] Example 1 Bionic micro-nano fractal structure polymer magnetic beads-1

[0063] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0064] a) 5 mL of α-methylstyrene, 2 mL of dichloromethane, 35 mg of benzoyl peroxide, and 120 mg of poly-α-methylstyrene were mixed and dispersed by ultrasonication for 20 min to obtain solution A;

[0065] b) adding 50 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 30 min to obtain dispersion B;

[0066] c) adding 100 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain a solution D;

[0067] d) Solution A and dispersion B were mixed and ultrasonically dispersed for 20 minutes; then, they were emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0068] e) mixing the oil-in-water emulsion C with the solution D, heating to 45°C to volatilize the solvent for 30 minutes, introducing nitrogen for 5 minutes, and stirring at 70°C for 12 hours to carry out polymerization reaction;

[0069] f) The product obtained by the reaction was repeatedly washed with ethanol and deionized water for three times and freeze-dried.

[0070] The SEM characterization showed that the synthesized biomimetic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 2μm. Figure 1 shown.

[0071] Example 2 Bionic micro-nano fractal structure polymer magnetic beads-2

[0072] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0073] a) 5 mL of α-methylstyrene, 2 mL of dichloromethane, 35 mg of benzoyl peroxide, and 120 mg of poly-α-methylstyrene were mixed and dispersed by ultrasonication for 20 min to obtain solution A;

[0074] b) adding 50 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 30 min to obtain dispersion B;

[0075] c) adding 150 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain solution D;

[0076] d) Solution A and dispersion B were mixed, ultrasonically dispersed for 20 min, and then emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0077] e) mixing the oil-in-water emulsion C with the solution D, heating to 45°C to volatilize the solvent for 30 minutes, introducing nitrogen for 5 minutes, and stirring at 70°C for 12 hours to carry out polymerization reaction;

[0078] f) The resulting solution was washed three times with ethanol and deionized water, and freeze-dried.

[0079] The SEM characterization showed that the synthesized biomimetic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 2.8 μm. Figure 2 shown.

[0080] Example 3 Bionic micro-nano fractal structure polymer magnetic beads-3

[0081] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0082] a) 5 mL of α-methylstyrene, 2 mL of dichloromethane, 35 mg of benzoyl peroxide, and 120 mg of polystyrene were mixed and ultrasonically dispersed for 20 min to obtain solution A;

[0083] b) adding 50 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 20 min to obtain dispersion B;

[0084] c) adding 200 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain a solution D;

[0085] d) Solution A and dispersion B were mixed, ultrasonically dispersed for 20 min, and then emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0086] e) mixing the oil-in-water emulsion C with the solution D, heating to 45°C to volatilize the solvent for 30 minutes, introducing nitrogen for 5 minutes, and stirring at 70°C for 12 hours to carry out polymerization reaction;

[0087] f) The product obtained by the reaction was repeatedly washed with ethanol and deionized water for three times and freeze-dried.

[0088] The SEM characterization showed that the synthesized biomimetic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 3.7 μm. Figure 3 Its TEM photo is shown as Figure 4 As shown, magnetic nanoparticles dispersed on the surface of the polymer core and burr structures distributed on the surface of the core can be seen.

[0089] Example 4 Bionic micro-nano fractal structure polymer magnetic beads-4

[0090] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0091] a) 5 mL of α-methylstyrene, 2 mL of dichloromethane, 35 mg of benzoyl peroxide, and 120 mg of polystyrene were mixed and ultrasonically dispersed for 20 min to obtain solution A;

[0092] b) adding 50 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 20 min to obtain dispersion B;

[0093] c) adding 250 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain solution D;

[0094] d) Solution A and dispersion B were mixed and ultrasonically dispersed for 30 minutes; then, they were emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0095] e) mixing the oil-in-water emulsion C with the solution D, heating to 45° C. to volatilize the solvent for 60 min, introducing nitrogen for 5 min, and stirring at 70° C. for 24 h to carry out polymerization reaction;

[0096] f) The product obtained by the reaction was washed repeatedly with methanol and ethanol for three times and freeze-dried.

[0097] The SEM characterization showed that the synthesized biomimetic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 4.3 μm. Figure 5 shown.

[0098] From the SEM photos of the polymer magnetic beads prepared in Examples 1-4, it can be found that as the amount of the hydrophilic monomer increases, the length of the burr-like micro-nano fractal structure on the surface of the prepared polymer magnetic beads increases.

[0099] Example 5: Polymer magnetic beads with biomimetic micro-nano fractal structures

[0100] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0101] a) 4 mL of vinyl n-butyl ether, 1 mL of dichloromethane, 20 mg of azobisisobutyronitrile, and 150 mg of polyvinyl n-butyl ether were mixed and dispersed by ultrasonication for 20 min to obtain solution A;

[0102] b) adding 30 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 20 min to obtain dispersion B;

[0103] c) adding 150 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain solution D;

[0104] d) Solution A and dispersion B were mixed and ultrasonically dispersed for 20 minutes; then, they were emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0105] e) mixing the oil-in-water emulsion C with the solution D, heating to 45° C. to volatilize the solvent for 30 min, introducing nitrogen for 5 min, and stirring at 70° C. for 24 h to carry out polymerization reaction;

[0106] f) The product obtained by the reaction was repeatedly washed with ethanol and deionized water for three times and freeze-dried.

[0107] The SEM characterization showed that the synthesized bionic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 6.3 μm.

[0108] Example 6: Polymer magnetic beads with biomimetic micro-nano fractal structures

[0109] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0110] a) 8 mL of 4-vinylbiphenyl, 2 mL of dichloromethane, 30 mg of benzoyl peroxide, and 150 mg of poly (4-vinylbiphenyl) were mixed and dispersed by ultrasonication for 20 min to obtain solution A;

[0111] b) adding 30 mg of manganese ferrite nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 20 min to obtain dispersion B;

[0112] c) adding 180 mg of sodium styrene sulfonate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain solution D;

[0113] d) Solution A and dispersion B were mixed, ultrasonically dispersed for 30 min, and then emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0114] e) mixing the oil-in-water emulsion C with the solution D, heating to 45° C. to volatilize the solvent for 45 min, introducing nitrogen for 5 min, and stirring at 70° C. for 12 h to carry out polymerization reaction;

[0115] f) The product obtained by the reaction was repeatedly washed with ethanol and deionized water for three times and freeze-dried.

[0116] The SEM characterization showed that the synthesized bionic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 4.6 μm.

[0117] Example 7: Polymer magnetic beads with biomimetic micro-nano fractal structures

[0118] A method for preparing polymer magnetic beads with bionic micro-nano fractal structures comprises the following steps:

[0119] a) 1.5 mL of α-methylstyrene, 1 mL of dichloromethane, 20 mg of azobisisobutyronitrile, and 100 mg of polystyrene were mixed and dispersed by ultrasonication for 20 min to obtain solution A;

[0120] b) adding 30 mg of ferrosoferric oxide nanoparticles to 3 mL of dichloromethane and ultrasonically dispersing for 20 min to obtain dispersion B;

[0121] c) adding 1100 mg of sodium styrene carboxylate to 10 mL of a 0.0030 g / mL aqueous sodium dodecyl sulfonate solution to obtain a solution D;

[0122] d) Solution A and dispersion B were mixed and ultrasonically dispersed for 20 minutes; then, they were emulsified with 45 mL of a 0.0030 g / mL sodium dodecyl sulfate aqueous solution to obtain an oil-in-water emulsion C;

[0123] e) mixing the oil-in-water emulsion C with the solution D, heating to 45°C to volatilize the solvent for 30 minutes, introducing nitrogen for 5 minutes, and stirring at 70°C for 12 hours to carry out polymerization reaction;

[0124] f) The product obtained by the reaction was repeatedly washed with methanol and deionized water for three times and freeze-dried.

[0125] The SEM characterization showed that the synthesized bionic micro-nano fractal polymer magnetic beads had a burr structure on the surface, good dispersion of the magnetic beads, and uniform size with an average particle size of 5.8 μm.

[0126] Application Examples

[0127] Application Example 1: Polymer magnetic beads with biomimetic micro-nano fractal structures are used to efficiently capture tumor cells

[0128] The biotinylated epithelial cell adhesion molecule antibody biotin-anti-EpCAM is loaded on the biomimetic micro-nano fractal polymer magnetic beads-3 obtained in Example 3 to identify and separate tumor cells.

[0129] a) Weigh 40 mg of biomimetic micro-nano fractal polymer magnetic beads, activate them with MES solution containing 5 mg / mL EDC and 5 mg / mL NHS, then modify streptavidin SA, and finally graft the antibody biotin-anti-EpCAM. The biomimetic micro-nano fractal polymer magnetic beads modified with antibodies are dispersed in PBS for later use.

[0130] b) Take the density as 10 5 1 mL of cell suspension with a concentration of 100 μg / mL was mixed with an appropriate amount of magnetic beads and incubated in an incubator for a period of time. The mixture was then separated using a magnetic separator and washed with PBS solution. The cells not captured by the polymer magnetic beads with bionic micro-nano fractal structure were suspended in PBS solution and the cells were counted. The enriched cells were detected using a cell counting plate and the capture efficiency was calculated.

[0131] The interaction between cells and biomimetic micro-nanofractal polymer magnetic beads was observed by scanning electron microscopy. Figure 6 As shown, a good topological interaction is formed between the polymer magnetic beads with bionic micro-nano fractal structures and the cells, and the cells extend their filopodia and wrap around the surface of the polymer magnetic beads with bionic micro-nano fractal structures.

[0132] The cell capture efficiency at different capture times was calculated. The results are shown in Figure 7 As shown, it can be seen that the capture efficiency of polymer magnetic beads-3 for tumor cells has reached a maximum of 88% within 30 minutes; while under experimental conditions, the capture efficiency of commercial magnetic beads Dynabeads M-280 only reached a maximum of 37% at 45 minutes, and the capture efficiency is much lower than that of the magnetic beads in the present invention.

[0133] Application Example 2: Highly efficient and specific targeting of tumor cells by polymer magnetic beads with biomimetic micro-nano fractal structures

[0134] The polymer magnetic beads prepared in Example 3 were used to capture tumor cells. The test process was exactly the same as that in Application Example 1, except that the types of cells to be captured were changed. The polymer magnetic beads were used to capture breast cancer cells (MCF-7), prostate cancer cells (PC-3), lymphoma cells (Daudi), and peripheral blood leukemia T cells (Jurkat). The capture efficiency of these four cells was as follows: Figure 8 As shown, it can be seen that the polymer magnetic beads prepared in the embodiment of the present invention have a high specific capture efficiency of 88% and 76% for tumor cells breast cancer cells (MCF-7) and prostate cancer cells (PC-3), respectively.

[0135] Application Example 3 Effect of the ratio of polymer magnetic beads with biomimetic micro-nano fractal structure to tumor cells on capture efficiency

[0136] The polymer magnetic beads prepared in Example 3 and the commercial magnetic beads Dynabeads M-280 were used to capture tumor cells. The test process was exactly the same as that in Application Example 1, except that the ratio of polymer magnetic beads to tumor cells was changed to 1:1, 2:1, 5:1, 10:1, and 100:1, respectively. The capture efficiency of polymer magnetic beads for tumor cells at different ratios was shown in FIG. Fig. 9 As shown in the figure, it can be seen that as the ratio of polymer magnetic beads to tumor cells increases, the capture efficiency of tumor cells also increases, and the maximum capture efficiency is 88%. Compared with the commercial magnetic beads Dynabeads M-280, the capture efficiency is 37% under the same capture time. The polymer magnetic beads achieve a higher capture efficiency when the ratio is lower.

[0137] Application Example 4 Effect of the micro-nano fractal structure length of polymer magnetic beads with biomimetic micro-nano fractal structure on capture efficiency

[0138] The polymer magnetic beads prepared in Examples 1-4, magnetic beads-1, magnetic beads-2, magnetic beads-3, and magnetic beads-4, were respectively selected for capturing tumor cells. The test process was exactly the same as that in Application Example 1, except that the type of polymer magnetic beads was changed. The results are shown in FIG. Fig.10 As shown, it can be seen that as the length of the micro-nano fractal structure on the surface of the polymer magnetic beads increases, the capture efficiency of tumor cells increases, with a maximum value of 89%.

[0139] Application Example 5: Biomimetic micro-nano fractal structure polymer magnetic beads for efficient capture of Staphylococcus aureus

[0140] a) 10 mg of biomimetic micro-nano fractal polymer magnetic beads were placed in a 1.5 mL centrifuge tube, and 0.5 mL of MES buffer solution with a pH of 6 was added to resuspend the beads, and the beads were separated by a magnetic stand, and the supernatant was discarded. The process was repeated three times;

[0141] b) Add 0.5 mL of MES buffer solution with a pH of 6 and mix well. Add 0.5 mL of activator EDC (5 mg / mL) and place in a mixer to react at room temperature for 40 min;

[0142] c) adding 100 μg of Staphylococcus aureus polyclonal antibody and reacting at room temperature for 18 hours; finally, adding 0.5 mL of blocking agent and reacting at room temperature for 4 hours;

[0143] d) washing the magnetic beads with 0.5 mL of PBS solution, separating them by magnetic stand, discarding the supernatant, and repeating this process three times to obtain Staphylococcus aureus immune magnetic beads;

[0144] e) Add 10 mL of the test solution to 90 mL of tryptone soy broth medium, inoculate Staphylococcus aureus, and culture at 36°C for 20 h to obtain a concentration of 10 3 CFU / mL of bacterial solution; at the same time, a control was made with a pure bacterial culture without adding a sample;

[0145] f) Take 1 mL of bacterial solution, add 100 μL of Staphylococcus aureus immune magnetic beads, and allow the immune reaction to proceed for 30 minutes;

[0146] g) The magnetic beads were magnetically separated from the bacterial solution under the action of a magnetic field for 5 minutes, and the number of bacteria captured by each immunomagnetic bead was counted, and the capture rate was calculated according to the following formula:

[0147] Capture efficiency = N c / N 0 ×100%,

[0148] Among them, N c It is the number of bacteria captured by the polymer magnetic beads with biomimetic micro-nano fractal structure, and the unit is CFU / 100μL;

[0149] N 0 It is the number of bacteria in the blank control, in units of CFU / 100 μL; the blank control is a pure culture of bacteria without adding a sample.

[0150] After comparison and calculation with the blank control, the bacteria capture rate reached 83%.

[0151] Application Example 6: Biomimetic micro-nano fractal polymer magnetic beads efficiently capture exosomes in concentrated / pre-enriched cell supernatant and are used for quantitative detection of exosomes

[0152] a) Add exosome-free culture medium to a culture dish with an MCF-7 cell density of about 80%, collect the culture medium after culturing for 2 days, centrifuge, and take the supernatant; filter the supernatant through a 0.22 μm filter membrane to obtain a cell supernatant without cells and apoptotic bodies. Concentrate 20 mL of the above culture medium to 120 μL through a 30KDa ultrafiltration tube to obtain a culture medium pre-enriched with exosomes.

[0153] b) Add 6 volumes of 0.12% (w / v) BSA solution and 0.002% (w / v) mouse IgG to 120 μL of cell supernatant treated with exosome concentration / pre-enrichment, mix well, add exosome capture magnetic beads containing 0.5 μg CD63 (an exosome surface-specific antibody) of the present invention (the mass ratio of CD63 to magnetic beads is 0.0005:1), and incubate overnight with rotation at 4°C to obtain magnetic beads that capture exosomes.

[0154] c) The magnetic beads that captured the exosomes were used to extract RNA using miRNeasy Serum / Plasma Advanced Kit (QIAGEN RNA extraction kit), and then the RNA was reverse transcribed into cDNA. 10 μL of reverse transcribed cDNA, 1 μL of GAPDH primer, 1 μL of enzyme-free water, and 10 μL of ddPCR TM Supermix for Probes (No dUTP) were added to each ddPCR well. After PCR amplification, the housekeeping gene GAPDH in the exosomes was quantified using Bio-Rad QX200 TM, and the content of the housekeeping gene GAPDH was used to reflect the content of the exosomes. The exosome content was calculated to be 84%.

[0155] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A polymer magnetic bead with a bionic micro-nano fractal structure, characterized in that: It includes a hydrophobic polymer core, magnetic nanoparticles dispersed inside and on the surface of the core, and a hydrophilic micro-nano fractal structure distributed on the surface of the core; The hydrophilic micro-nano fractal structure has a burr-like morphology; The length of the hydrophilic micro-nano fractal structure is 0 to 2500 nm, but excluding 0; the diameter is 50 nm to 300 nm; The material of the hydrophilic micro-nano fractal structure is selected from one or more of sodium polyacrylate, sodium polymethacrylate, sodium polyitaconate, sodium polymaleate, sodium polyvinyl sulfonate, sodium polystyrene sulfonate, sodium polystyrene carboxylate, and sodium polystyrene borate; The diameter of the hydrophobic polymer core is 100nm~100μm; The material of the hydrophobic polymer core is selected from one or more of polystyrene, poly-α-methylstyrene, poly-o-chlorostyrene, polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride.

2. The polymer magnetic beads with bionic micro-nano fractal structure according to claim 1, characterized in that: The polymer magnetic beads have superparamagnetism and a particle size of 100nm-100μm.

3. The polymer magnetic beads with biomimetic micro-nano fractal structure according to claim 1, characterized in that: The particle size of the magnetic nanoparticles is 1 nm to 1000 nm.

4. The polymer magnetic beads with bionic micro-nano fractal structure according to claim 1 or 3, characterized in that: The magnetic nanoparticles are selected from one or more of ferroferric oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron platinum nanoparticles, cobalt triplatinide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles.

5. A method for preparing polymer magnetic beads with bionic micro-nano fractal structures as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1, dissolving a hydrophobic monomer, an initiator, and a hydrophobic polymer in an organic solvent to obtain a solution A; dispersing magnetic nanoparticles in an organic solvent to obtain a dispersion B; mixing the solution A and the dispersion B evenly, and emulsifying them by adding a surfactant aqueous solution to obtain an oil-in-water emulsion C; S2, dissolving the hydrophilic monomer in an aqueous surfactant solution to obtain a solution D; S3, mixing the oil-in-water emulsion C and the solution D, heating to volatilize the organic solvent, introducing nitrogen, and after the polymerization reaction, washing and freeze-drying the product to obtain.

6. The preparation method according to claim 5, characterized in that: The weight average molecular weight of the hydrophobic polymer is 1000 g / mol to 80000 g / mol; the concentration of the hydrophobic polymer in solution A is 0.05 mg / mL to 500 mg / mL.

7. The preparation method according to claim 5, characterized in that: The mass ratio of hydrophobic monomer to magnetic nanoparticles used in the preparation process is 10~300:

1.

8. The preparation method according to claim 5, characterized in that: The molar ratio of the hydrophobic monomer to the hydrophilic monomer is 0.1-200:

1.

9. The preparation method according to claim 5, characterized in that: The molar ratio of the initiator to the hydrophilic monomer is 0.01-0.1:

1.

10. The preparation method according to claim 5, characterized in that: After the oil-in-water emulsion C and solution D are mixed in S3, The ratio of the molar amount of the hydrophobic monomer to the volume of the surfactant aqueous solution is 0.005mmol~15mmol:1mL; The ratio of the initiator molar amount to the surfactant aqueous solution volume is 0.003mmol~0.3mmol:1mL; The ratio of the molar amount of the hydrophilic monomer to the volume of the surfactant aqueous solution is 0.005 mmol~15mmol:1mL.

11. Use of the bionic micro-nano fractal polymer magnetic beads according to any one of claims 1 to 4 in immunoassay, nucleic acid separation and extraction, cell sorting, bacteria capture, virus capture, and enzyme fixation.